Strengthening Citizenship Attitudes Through Civil Society in Elementary School Students in Mandailing Natal - Siregar, Parulian; Namiroh Lubis; Asrin Nasution; Arafatul Soraya (International Journal of Basic Educational Research, 2024)
The decline in citizenship attitudes among elementary school students is a significant concern requiring urgent attention. Citizenship attitudes, encompassing consciousness, responsibility, participation, and loyalty as Indonesian citizens, are crucial in molding individuals who contribute positively to national life. Recent incidents of bullying, violence, and intolerance in elementary schools across Indonesia highlight a disturbing trend, emphasizing the urgent need for action. Bullying incidents, particularly in Mandailing Natal District, persist due to factors like seniority culture and lack of empathy, exacerbating students' vulnerability. To address this decline, civil society's role is essential, yet its full potential remains untapped due to various constraints. Understanding this background is crucial for effective intervention design. Civil society can reinforce citizenship attitudes, advocate social righteousness, and enhance national integration, emphasizing values like legal awareness, social responsibility, and tolerance. Child-friendly school environments and active participation in civil society programs can empower students and foster inclusive communities. Strengthening citizenship attitudes requires curriculum integration, extracurricular activities, and teacher training to enhance students' awareness and critical thinking. Collaborative efforts involving schools, teachers, students, and the local community are vital, along with investment in resources and partnerships. By reinforcing citizenship attitudes, we can cultivate individuals committed to democracy, tolerance, and social responsibility, fostering a harmonious and inclusive society.